2017
DOI: 10.1038/tp.2017.123
|View full text |Cite
|
Sign up to set email alerts
|

Combined assessment of DYRK1A, BDNF and homocysteine levels as diagnostic marker for Alzheimer’s disease

Abstract: Early identification of Alzheimer’s disease (AD) risk factors would aid development of interventions to delay the onset of dementia, but current biomarkers are invasive and/or costly to assess. Validated plasma biomarkers would circumvent these challenges. We previously identified the kinase DYRK1A in plasma. To validate DYRK1A as a biomarker for AD diagnosis, we assessed the levels of DYRK1A and the related markers brain-derived neurotrophic factor (BDNF) and homocysteine in two unrelated AD patient cohorts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
(63 reference statements)
5
26
0
Order By: Relevance
“…Accumulating evidence showed the deleterious effects of HHcy through inducing oxidative stress and its downstream effects, thus leading to the development or potentiation of AD-like pathologies including memory impairments [ 23–25, 48 ]. HHcy could also be a potential diagnostic marker in AD [ 49 ]. To evaluate the effect of MO intervention on the Hcy induced cognitive impairments, Morris Water Maze (MWM) test was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence showed the deleterious effects of HHcy through inducing oxidative stress and its downstream effects, thus leading to the development or potentiation of AD-like pathologies including memory impairments [ 23–25, 48 ]. HHcy could also be a potential diagnostic marker in AD [ 49 ]. To evaluate the effect of MO intervention on the Hcy induced cognitive impairments, Morris Water Maze (MWM) test was carried out.…”
Section: Resultsmentioning
confidence: 99%
“…By now, some notions about Alzheimer's disease hold true (Hung et al, 2016 ): (i) neurons are the primary cells dying, by apoptosis, in brains; (ii) plaques conduct to develop death enzymes in neurons, such as caspases, in particular, caspase 6 is an apoptotic cysteine protease which induces disease progression promoting neurodegeneration (Vaidya et al, 2011 ); (iii) brain derived neurotrophic factor (BDNF) has several roles in synaptic plasticity and neuronal survival and it is downregulated in Alzheimer's disease (Janel et al, 2017 ); (iv) in Alzheimer patients, function and levels of adhesion molecules viable for synapses are affected, e.g., synaptic cell adhesion molecules which are glycoproteins of cell surface (Leshchyns'ka and Sytnyk, 2016 ) (v) Alzheimer brains are characterized by a decrease of neurotransmitters, primary acetylcholine, but also catecholamine, glutamate, and serotonin (Selkoe and Schenk, 2003 ; Hung et al, 2016 ).…”
Section: Exosomes In Chronic Neurodegenerative Diseasesmentioning
confidence: 99%
“…For instance, HHcy is brought into the connection to cognitive decline, it has been practically demonstrated that there is a positive correlation between increased values of Hcy and reduction of cognitive functions(Setién-Suero et al 2016). One of the most studied form of cognitive impairment certainly is Alzheimer's it has been shown that Hcy is one of the risk factors(Janel et al 2017; Moretti et al. 2017).…”
mentioning
confidence: 99%